Новые органопластики конструкционного назначения - Чигвінцева, Ольга Павлівна; Chigvintseva, Olga; Токар, Андрій Володимирович; Tokar, Andrey; Сінчук, Олена Володимирівна; Synchuk, Yelena; Варлан, Костянтин Єлисейович; Varlan, Konstantin; Радіонов, Андрій Юрійович; Radionov Andrey, Andrey (Бял ГРАД-БГ ОДД, 2017)
Вивчено вплив природи поліефір-ного в’яжучого на структуру і вла-стивості полімерних композитів, армованих органічним волокном. Армування поліефірів поліарилат і пентапласт арамідним волокном терлон покращує основні експлуа-таційні характеристики розробле-них полімерних композитів. The influence of the nature of the polyester binder on the structure and properties of polymer composites reinforced with organic fiber has been studied. The reinforcement of polyesters of polyarylate and penta-plast with aramid fiber terlon im-proves the main performance charac-teristics of the developed polymer composites.
Нові органопластики конструкційного призначення
New organoplastics constructional purpose
Keywords: пентапласт; pentaplast; поліарилат; polyarylate; органічне волокно; organic fiber; структура; structure